HUMAN TRAFFICKING DAN SOLUSINYA DALAM PERSPEKTIF HUKUM ISLAM - Basri, Rusdaya (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2012)
This article discusses the problem of human trafficking and the solution in the perspective of Islamic law. Human Trafficking is